Padrões de distribuição espacial e temporal da recidiva da Hanseníase no Brasil e seus fatores associados de 2001 – 2022 - Boigny, Reagan Nzundu (2024)
Leprosy is a chronic infectious disease that primarily affects peripheral nerves, skin and mucous membranes. The occurrence of leprosy recurrence significantly impacts leprosy control as a public health problem. The objective of this thesis was to characterize the spatial and temporal distribution of leprosy relapse in Brazil and its associated factors in the period from 2001 to 2022. The study was organized in 3 steps, based on cases of leprosy relapse reported in the Notifiable Diseases Information System. There was 1 cross-sectional and ecological study (1), 1 ecological study (2) and 1 retrospective cohort study (3): step 1 – magnitude and temporal trend of leprosy relapse cases in the state of Ceará in the period 2001-2018; step 2 – temporal trends and spatial-temporal approach of distribution of cases of leprosy recurrence in Brazil, from 2001 to 2021; step 3 – associated factors for the occurrence of leprosy relapse in Brazil from 2001 to 2022. The data were organized in Stata 15.1. The temporal and space-time analyses were carried out, respectively, by Joinpoint Regression Program 4.0.4 and SaTScan 9.6, all maps were made by ArcMap 9.2. In Ceará, 1,777 leprosy relapse cases were diagnosed. Higher prevalence of relapse was found in men (PR=1.58; 95%CI:1.44–1.74), Illiterate (PR=1.99; 95%CI:1.30–3.06), mixed race (PR=1.27; 95%CI:1.11–1.46), multibacilar (PR=4.16; 95%CI:3.63–4.77), lepromatous (PR=4.55; 95%CI:3.77–5.48) and persons with visible disabilities (PR=2.67; 95%CI:2.32–3.07). The proportion of relapse tended to increase throughout the study period (4,9%; 95%CI:3.1–6.9). A total of 31 334 patients who experienced leprosy relapse were identified. The number of recurrent cases tended to increase throughout the study period, and this increase was significant among females and in almost all age groups, except for those < 15, 50–59 and ≥70 y. Several clusters of high- and low-risk patients were identified across all regions with a heterogeneous distribution. In the period analyzed, 17,480 records were considered as true pairs and the mean time (in months) between the diagnosis of a new case and the occurrence of relapse was 6.4 months (± 4.59 months). There was a predominance of males, black skin color (mixture of brown and black), with elementary education and between the ages of 30 and 59. Clinically, the borderline and virchowian forms predominated, as well as multibacillary cases without physical disabilities at the time of diagnosis. Sex, having completed elementary school, high school, clinical forms and operational classification remained associated with the occurrence of relapse. The burden of recurrence is on an increasing trend, concentrated in some groups, distributed across all regions. The time for occurrence of relapse was considered short considering the characteristics and natural history of the disease. Some clinical and social characteristics were associated with the occurrence.